2019
DOI: 10.1016/j.ygeno.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle titanium dioxide affects the growth and microRNA expression of switchgrass (Panicum virgatum)

Abstract: Nanoparticle TiO is a common chemical used in daily life. As increasing usage of TiO, it is becoming a potentially dangerous contaminant to the environment. However, the impact of TiO is not well understood. In this paper, switchgrass was employed to investigate the impacts of nanoparticle TiO on plant growth and development as well as the potential impact on the expression of microRNAs (miRNAs). TiO significantly affected switchgrass seed generation as well as plant growth and development in a dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…However, Wu et al ( 2017 ) found in their experiment with Oryza sativa L. a decrease in the biomass of the roots and leaves of plants exposed to concentrations of TiO 2 -ENPs of 100, 250, or 500 mg L −1 , and also an increase was observed in antioxidant activity in response to stress produced by ENPs. Similarly, Boykov et al ( 2014 ) reported that as TiO 2 -ENPs concentration increased, biomass production decreased while TiO 2 -ENPs negatively affected microRNA expressions.…”
Section: Resultsmentioning
confidence: 87%
“…However, Wu et al ( 2017 ) found in their experiment with Oryza sativa L. a decrease in the biomass of the roots and leaves of plants exposed to concentrations of TiO 2 -ENPs of 100, 250, or 500 mg L −1 , and also an increase was observed in antioxidant activity in response to stress produced by ENPs. Similarly, Boykov et al ( 2014 ) reported that as TiO 2 -ENPs concentration increased, biomass production decreased while TiO 2 -ENPs negatively affected microRNA expressions.…”
Section: Resultsmentioning
confidence: 87%
“…As an example, an abscisic acid-dependent pathway is reported for plants subjected to gradual water stress by withholding irrigation in which, miR169 transcripts are down-regulated during the stress 60 . Furthermore, it has been recently shown that among the plant miRNAs, miRNA-169 is the only miRNA that is inhibited by titanium dioxide nanoparticles with a dose-dependent pattern 61 . During the last two decades, titanium dioxide has become a potentially dangerous contaminant to the environment which undesirably affects the plant growth and development 62 .…”
Section: Resultsmentioning
confidence: 99%
“…The same situation is relevant in plant responses to metal NPs. In switchgrass seedlings treated with 0.1-1% TiO 2 NPs, the expression of miR156 and miR159 increased [78]. Yu et al (2019) [79] indicated that miR156 and miR159 in wild barley seedlings might be related to Cd tolerance.…”
Section: Effect Of Fe 3 O 4 Nanoparticles On Barley Mirna Expressionmentioning
confidence: 96%